Global sixties in sound and vision : media, counterculture, revolt - Brown, Timothy Scott 1961- Hrsg (Palgrave Macmillan, 2014)
Red noise : pop and politics in post-1968 France / Jonathyne Briggs -- Mapping tropicalia / Christopher Dunn -- Magical mystery tours : Godard and Antonioni in America / David Fresko -- Opening and activating a depth dimension : the politics of privacy in the new American cinema / Josh Guilford -- Utopia and dystopia in the science fiction film circa 1968 / Kathrin Fahlenbrach -- "Art is love is god" : language and sound in Wallace Berman's Aleph, 1956-66 / Chelsea Behle Fralick -- Guitar smashing / Wolfgang Kraushaar -- "The revolution is over, and we have won!" : Alfred Hilsberg, West German punk and the sixties / Jeff Hayton -- The sun and moon have come together : fourth way, liberatory aesthetics and countercultural spirituality / Kevin Fellezs -- "A weapon in our struggle for liberation" : black arts, black power, and the 1969 pan-African cultural festival / Samir Meghelli -- The revolution will not be televised, but it will be recorded : soul, funk, and the black urban experience, 1968-1979 / Francesca D'Amico -- Jukebox modernism : the transatlantic sight and sound of Peter Blake's Got a girl (1960-61) / Melissa Mednicov -- Uninteresting pictures : art and the anti-humanism of 1968 / Joshua Shannon -- And the future of information / Andrew Lison